Band Engineering Induced Conducting 2H‐Phase MoS2 by PdSRe Sites Modification for Hydrogen Evolution Reaction. Issue 12 (12th February 2022) - Luo, Zhaoyan; Li, Junjie; Li, Yongliang; Wu, Duojie; Zhang, Lei; Ren, Xiangzhong; He, Chuanxin; Zhang, Qianling; Gu, Meng; Sun, Xueliang
Abstract: The electronic band structure of MoS2 exerts far‐ranging effects on the applications of these materials, ranging from chemical catalysis, electronic, and magnetic behaviors. However, the underlying relationship between the electronic band structure and activity is largely unknown in heterogeneous catalysis including the hydrogen evolution reaction, partly due to the lack of a controllable methodology to achieve desirable electronic band structures in the 2H‐phase MoS2 . Herein it is demonstrated that dual dopants can engineer the band structure of MoS2 by substituting into the adjacent Mo sites. Specifically, these constructed PdRe dimers bridged by sulfur (PdSRe sites) introduce conducting electronic states around the Fermi level to increase the metallic characteristics of MoS2, resulting in metallic‐like behavior, which is initially semiconducting. Furthermore, the efficacy of inducing a phase conversion from 2H to metallic 1T is higher for codoping with dual dopants as compared to that for the use of a single dopant, thereby generating more intrinsically active PdS*Mo sites to further increase active sites density. Ultimately, this leads to the MoS2 catalyst showing a low overpotential of 46 mV at a current density of 10 mA cm −2 and a high exchange current density of 1.524 mA cm −2, along with superior operating durability. Abstract : A neighboring dual‐heteroatom doping strategy is proposed to effectively tune electronic band structures. Specifically, these constructed PdRe dimers bridged by sulfur introduce conducting electronic states around the Fermi level to increase the metallic characteristics of MoS2, resulting in a metallic‐like behaviour, which is initially semiconducting. The Pd, Re‐MoS2 yields the highest hydrogen evolution reaction performance achieved thus far using phase‐pure MoS2 ‐based materials.